Semi‐interpenetrating gel polymer electrolyte based on PVDF‐HFP for lithium ion batteries. Issue 11 (5th October 2020) - Luo, Kaili; Shao, Dingsheng; Yang, Li; Liu, Lei; Chen, Xiaoyi; Zou, Changfei; Wang, Dong; Luo, Zhigao; Wang, Xianyou
Abstract: Poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP)‐based gel polymer electrolyte (GPE) is considered one of the promising candidate electrolytes in the polymer lithium ion battery (LIB) because of its free standing, shape versatility, security, flexibility, lightweight, reliability, and so on. However, the pristine PVDF‐HFP GPE cannot still meet the requirement of large‐scale LIBs and other electrochemical devices due to its relatively low ionic conductivity and deterioration of mechanical strength caused by the incorporation of organic liquid electrolyte into the polymer matrix as well as high cost. In order to overcome above deficiencies of PVDF‐HFP based GPE, ultraviolet (UV)‐curable semi‐interpenetrating polymer network is designed and synthesized through UV‐irradiation technique, and the as‐prepared semi‐interpenetrating matrix is constituted by pentaerythritol tetracrylate polymer network and PVDF‐HFP. The ionic conductivity of the optimized GPE is as high as 5 × 10 −4  S/cm and electrochemical window is up to 4.8 V at room temperature. Especially, the LIB prepared by GPE shows the high initial discharge specific capacity of 151 mAh/g at 0.5 C and good rate capability. Therefore, the semi‐interpenetrating GPE based on PVDF‐HFP exhibits a promising prospect for the application of rechargeable LIBs. Abstract : A novel semi‐interpenetrating gel polymer electrolyte membrane is constituted by poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) and pentaerythritol tetracrylate (PETEA) polymer network through UV‐irradiation technique. The ionic conductivity is 5 × 10−4 S cm−1 and electrochemical window is up to 4.8 V at room temperature. More significantly, The batteries of PVDF‐HFP/PETEA GPE show the high initial discharge specific capacity of 151 mAh g‐1 at 0.5 C and good rate capability.Hence, the present study demonstrates that the UV‐irradiated PVDF‐HFP/PETEA membrane has great application potential in next generation of high‐performance lithium batteries.